Exploring the Implementation of Qur'anic Healing for Students Experiencing Academic Burnout - Nur Maslikhatun Nisak; Ruli Astuti; Eko Budi Supriyanto (Grief and Trauma, 2026)
This study aims to describe the implementation of Qur'anic Healing in relation to academic burnout in an educational institution. Academic burnout refers to a condition of physical, emotional, and mental exhaustion resulting from academic demands, characterized by exhaustion, cynicism toward academic activities, and reduced academic efficacy. This study employed a descriptive qualitative field research design. Data were collected through observations, semi-structured interviews, and documentation involving eight purposively selected participants, consisting of one principal, one vice principal for curriculum, three teachers, and three students, who were directly involved in the Qur'anic Healing program and had experience or understanding of students' academic burnout. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. The findings indicate that the implementation of Qur'anic Healing in the school is organized through three main practices: Qur'anic recitation, dhikr and Qur'anic supplication, and the internalization of Qur'anic values such as patience, gratitude, tawakal, and optimism. Participants reported that these practices were associated with experiences of psychological calmness, improved learning focus, reduced academic anxiety, and stronger learning motivation and self-confidence. The findings also suggest that teachers and students perceived these spiritual practices as helping students cope with symptoms commonly associated with academic burnout, including learning fatigue, boredom with academic activities, and reduced academic self-confidence. These findings describe how Qur'anic Healing is implemented and perceived as a spiritual approach for supporting students' psychological well-being within the educational setting.